Cover Feature: Spray‐Flame‐Prepared LaCo1–xFexO3 Perovskite Nanoparticles as Active OER Catalysts: Influence of Fe Content and Low‐Temperature Heating (ChemElectroChem 12/2020). Issue 12 (18th May 2020) - Alkan, Baris; Medina, Danea; Landers, Joachim; Heidelmann, Markus; Hagemann, Ulrich; Salamon, Soma; Andronescu, Corina; Wende, Heiko; Schulz, Christof; Schuhmann, Wolfgang; Wiggers, Hartmut
Abstract : The Cover Feature shows a spray‐flame reactor used to synthesize perovskite catalyst nanoparticles. The blue methane/oxygen pilot flame at the bottom ignites a combustible precursor aerosol injected via a centric nozzle. Nanoparticle formation downstream of the reaction zone leads to metastable, highly active LaCo1– x Fex O3 perovskite catalysts with improved oxygen evolution reaction activity. The image was taken by Samer Suleiman. More information can be found in the Aricle by B. Alkan et al .